2016
DOI: 10.1055/s-0035-1570751
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Fever after Acute Traumatic Spinal Cord Injury: A Qualitative Systematic Review

Abstract: Study Design  Systematic review.Objective  To determine the incidence, pathogenesis, and clinical outcomes related to neurogenic fevers following traumatic spinal cord injury (SCI).Methods  A systematic review of the literature was performed on thermodysregulation secondary to acute traumatic SCI in adult patients. A literature search was performed using PubMed (MEDLINE), Cochrane Central Register of Controlled Trials, and Scopus. Using strict inclusion and exclusion criteria, seven relevant articles were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
(89 reference statements)
1
11
0
2
Order By: Relevance
“…[11][12][13]15,18,19 Savage et al identified "neurogenic fever" in approximately one out of every in every 20-25 patients. 20 The frequency of non-infectious fever among our patients was comparable to the rate reported by Savage et al…”
Section: Discussionsupporting
confidence: 91%
“…[11][12][13]15,18,19 Savage et al identified "neurogenic fever" in approximately one out of every in every 20-25 patients. 20 The frequency of non-infectious fever among our patients was comparable to the rate reported by Savage et al…”
Section: Discussionsupporting
confidence: 91%
“…Another possible limitation of our study is that we did not include body temperature and medication data in our model. It is important to consider, however, that common accepted causes of fever in this patient population 47 are indirectly controlled by the inclusion of SCI level and severity, overall trauma severity/NISS and infections as covariates. Although data are scarce, there is also little evidence to suggest that haemodynamic management in the pre‐hospital setting overtly influences the circulating WBC response to acute CNS injury, 48 and clinical management was otherwise the same for all patients; high‐dose steroid treatment was also not routinely administered as per the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible limitation of our study is that we did not include body temperature and medication data in our model. It is important to consider, however, that common accepted causes of fever in this patient population 47 are indirectly controlled by the inclusion of SCI level and severity, overall trauma severity/NISS and infections as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the fever is central (neurogenic) in origin, antipyretics may be ineffective. Drugs that have proved effective in individual cases of central hyperthermia include baclofen, bromocriptine, amantadine, dantrolene, and propranolol, but these are unlikely to be widely available in developing countries [ 30 ].…”
Section: Care Of Patients With Confirmed Rabies Encephalomyelitismentioning
confidence: 99%